Peran Pendidikan Inklusif: Strategi dan Tantangan dalam Penghapusan Diskriminasi terhadap Anak-Anak Berkebutuhan Khusus - Fuji Astuti, Rahayu; Ani Putri, Khairunnisa (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This study seeks to gain a thorough understanding of the experiences of children with special needs in inclusive education and efforts to eliminate discrimination against them in schools that provide inclusive education. The approach utilized in this research is qualitative, which allows for in-depth information gathering through conducting interviews, observations and analyzing documents. The outcomes show the need for supportive policies, customized school services, adjustments to learning materials, and active participation of parents in promoting the development of children with disabilities. In addition, Islamic views also emphasize the importance of eliminating discrimination against children with disabilities by emphasizing human values such as respect, justice, care, solidarity, humanity, diversity and human rights. These values align with the principles of inclusive education which aims to create a fair and friendly environment for all children. This research is anticipated to contribute to science, especially in developing more effective and humane inclusive education policies and practices, as well as promoting the formation of an inclusive and just society for all individuals, including children with special needs.